التفكير الاحصائي وعلاقته بالذكاء المنطقي الرياضي لدى طلبة قسم الرياضيات في كلية التربية بالجامعة المستنصرية (Journal of the College of Basic Education, 2022)
The current research aims to identifyStatistical thinking for department of Mathematics Students at the Faculty of Education , Mustansiriya UniversityLogical mathematical intelligence for department of Mathematics Students at the Faculty of Education , Mustansiriya UniversityThe nature of the correlation relationship and its direction between the statistical thinking and logic mathematical intelligence for department of Mathematics Students at the Faculty of Education , Mustansiriya University The sample consisted of (200) students from the fourth stage Faculty of Education in Mustansiriya University, In order to achieve the objectives of the research and the collection of the private data, two tests one of them Statistical thinking and the other Logical mathematical intelligence ,were conducted and applied to a survey sample to verify the veracity of the paragraphs of each test and its instructions and to determine its time and conduct the appropriate statistical analyzes. The two tests were ready to be applied to the research group and in their final form. The paragraphs of the test of statistical thinking (24) and the mathematical logical intelligence test (16). The researchers used the statistical bag (spss to analyze the results by extracting the arithmetic average, standard deviation, T-Test for one sample and correlation coefficient Pearson, and the results indicated that students of the fourth stage in the Department of Mathematics at the Faculty of Education, University of Mustansiriya possess the statistical thinking and mathematical logic more than the average satisfactory for both tests as well as a positive correlation relationship bettwen statistical thinking and logical mathematical intelligence at the fourth stage students in the Department of Mathematics at the College of Education Mustansiriya University, and researchers presented a set of proposals and recommendations